Altered innate immune profile in blood of systemic mastocytosis patients. Issue 6 (14th June 2022) - Pérez‐Pons, Alba; Jara‐Acevedo, María; Henriques, Ana; Navarro‐Navarro, Paula; García‐Montero, Andrés C.; Álvarez‐Twose, Iván; Pedreira, Carlos E.; Sánchez‐Muñoz, Laura; Damasceno, Daniela; Caldas, Carolina; Muñoz‐González, Javier I.; Matito, Almudena; et al.
Abstract: Background: Mast cells (MC) from systemic mastocytosis (SM) patients release MC mediators that lead to an altered microenvironment with potential consequences on innate immune cells, such as monocytes and dendritic cells (DC). Here we investigated the distribution and functional behaviour of different populations of blood monocytes and DC among distinct diagnostic subtypes of SM. Methods: Overall, we studied 115 SM patients ‐ 45 bone marrow mastocytosis (BMM), 61 indolent SM (ISM), 9 aggressive SM (ASM)‐ and 32 healthy donors (HD). Spontaneous and in vitro ‐stimulated cytokine production by blood monocytes, and their plasma levels, together with the distribution of different subsets of blood monocytes and DCs, were investigated. Results: SM patients showed increased plasma levels and spontaneous production by blood monocytes of IL1β, IL6, IL8, TNFα and IL10, associated with an exhausted ability of LPS + IFNγ‐stimulated blood monocytes to produce IL1β and TGFβ. SM (particularly ISM) patients also showed decreased counts of total monocytes, at the expense of intermediate monocytes and non‐classical monocytes. Interestingly, while ISM and ASM patients had decreased numbers of plasmacytoid DC and myeloid DC (and their major subsets) in blood, an expansion of AXL + DC was specifically encountered in BMM cases. Conclusion: These results demonstrate an altered distribution of blood monocytes and DC subsets in SM associated with constitutive activation of functionally impaired blood monocytes and increased plasma levels of a wide variety of inflammatory cytokines, reflecting broad activation of the innate immune response in mastocytosis.